The equation that describes the proportional relationship between the cost and the number of days is:
A. y = 26x
The given graph shows the cost of keeping a toddler at KinderBlush daycare center.
In the graph, y represents the cost for keeping a toddler at the daycare center and x represents the number of days. Which equation describes the proportional relationship between the cost and the number of days?
A.
y = 26x
B.
y = 52x
C.
x = 26y
D.
x = 52y
11 answers
Simplify 9g−7h−6g + 2h
To simplify the given expression 9g - 7h - 6g + 2h, we can combine like terms:
9g - 6g - 7h + 2h
Combining the g terms, we have:
(9g - 6g) - 7h + 2h = 3g - 7h + 2h
And combining the h terms, we have:
3g - (7h - 2h) = 3g - 5h
Thus, the simplified expression is 3g - 5h.
9g - 6g - 7h + 2h
Combining the g terms, we have:
(9g - 6g) - 7h + 2h = 3g - 7h + 2h
And combining the h terms, we have:
3g - (7h - 2h) = 3g - 5h
Thus, the simplified expression is 3g - 5h.
Simplify 12e − 5f − 7e +3f
To simplify the given expression 12e - 5f - 7e + 3f, we can combine like terms:
12e - 7e - 5f + 3f
Combining the e terms, we have:
(12e - 7e) - 5f + 3f = 5e - 5f + 3f
And combining the f terms, we have:
5e - (5f - 3f) = 5e - 2f
Thus, the simplified expression is 5e - 2f.
12e - 7e - 5f + 3f
Combining the e terms, we have:
(12e - 7e) - 5f + 3f = 5e - 5f + 3f
And combining the f terms, we have:
5e - (5f - 3f) = 5e - 2f
Thus, the simplified expression is 5e - 2f.
Simplify 9x + 3y − 6 − 5x + 4y −3
To simplify the given expression 9x + 3y - 6 - 5x + 4y - 3, we can combine like terms:
9x - 5x + 3y + 4y - 6 - 3
Combining the x terms, we have:
(9x - 5x) + 3y + 4y - 6 - 3 = 4x + 3y + 4y - 6 - 3
Combining the y terms, we have:
4x + (3y + 4y) - 6 - 3 = 4x + 7y - 6 - 3
Combining the constants, we have:
4x + 7y - (6 + 3) = 4x + 7y - 9
Thus, the simplified expression is 4x + 7y - 9.
9x - 5x + 3y + 4y - 6 - 3
Combining the x terms, we have:
(9x - 5x) + 3y + 4y - 6 - 3 = 4x + 3y + 4y - 6 - 3
Combining the y terms, we have:
4x + (3y + 4y) - 6 - 3 = 4x + 7y - 6 - 3
Combining the constants, we have:
4x + 7y - (6 + 3) = 4x + 7y - 9
Thus, the simplified expression is 4x + 7y - 9.
Simplify 3/10x + 1/6y + 3/10x + 3/6y . Be sure to reduce any fractions to the lowest terms.
To simplify the given expression 3/10x + 1/6y + 3/10x + 3/6y, we can combine like terms:
3/10x + 3/10x + 1/6y + 3/6y
Combining the x terms, we have:
(3/10x + 3/10x) + 1/6y + 3/6y = 6/10x + 1/6y + 3/6y
Combining the y terms, we have:
6/10x + (1/6y + 3/6y) = 6/10x + 4/6y
Reducing the fractions, we have:
6/10x + (1/6 + 3/6)y = 6/10x + 4/6y
Both 6/10 and 4/6 can be simplified to 3/5:
(3/5)x + (3/5)y
Thus, the simplified expression is (3/5)x + (3/5)y.
3/10x + 3/10x + 1/6y + 3/6y
Combining the x terms, we have:
(3/10x + 3/10x) + 1/6y + 3/6y = 6/10x + 1/6y + 3/6y
Combining the y terms, we have:
6/10x + (1/6y + 3/6y) = 6/10x + 4/6y
Reducing the fractions, we have:
6/10x + (1/6 + 3/6)y = 6/10x + 4/6y
Both 6/10 and 4/6 can be simplified to 3/5:
(3/5)x + (3/5)y
Thus, the simplified expression is (3/5)x + (3/5)y.
wrong
Apologies for the mistake. Let's correct the simplification.
To simplify the expression 3/10x + 1/6y + 3/10x + 3/6y, we can combine like terms:
First, let's add the terms with x:
3/10x + 3/10x = 6/10x = 3/5x
Next, let's add the terms with y:
1/6y + 3/6y = 4/6y = 2/3y
Putting the simplified terms together, we have:
3/5x + 2/3y
Thus, the simplified expression is 3/5x + 2/3y.
To simplify the expression 3/10x + 1/6y + 3/10x + 3/6y, we can combine like terms:
First, let's add the terms with x:
3/10x + 3/10x = 6/10x = 3/5x
Next, let's add the terms with y:
1/6y + 3/6y = 4/6y = 2/3y
Putting the simplified terms together, we have:
3/5x + 2/3y
Thus, the simplified expression is 3/5x + 2/3y.